Local Residual Error Estimators for the Method of Moments Solution of Electromagnetic Integral Equations - Saeed, Usman; Peterson, Andrew F. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
Several methods for estimating the local (cell-by-cell) error associated with a method of moments solution of the electric field integral equation are investigated. Three different residual error estimators are used with a variety of prototype structures. The global error estimates show reasonable correlation with the actual current density errors, and all three local error estimators correctly identify the high-error regions. Utility of the proposed error estimators is presented through a simple h-refinement technique.